Academic Senate Minutes 2020-04-30 - Academic Senate:::::::::
Agenda approved. Minutes of 5/2 and 8/22 approved. Chair Report. President Report. Question for Provost. Question for the Statewide Senator. Vice Chair Report. Vice President of Administration and Finance Report. Chief Student Affairs Officer Report. EPC Report. FSAC Report. CFA Report. Revision to ENSP Water Resource Management BS and BA approved for Senate consent calendar. SAC Report. Associated Students Report. Sustainability Executive Committee Report. Senate Agenda approved.